Analysis of Logistics Cost Efficiency in Indonesia's Transportation System - Syifa, Given abi; Tohir, Muhammad (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
Indonesia's logistics costs remain high, at around 23-24% of PDB, well above the global average and that of other Southeast Asian countries, reducing national competitiveness. Land transportation contributes about 50% of domestic logistics costs. Multimodal transportation-combining multiple modes under one contract-is an efficient solution by simplifying administration and lowering costs. The national logistics system (Sislognas) continues to be developed through technology investment and stakeholder collaboration. Initiatives such as the National Logistics Ecosystem (NLE) and Indonesia National Single Window (INSW) 2.0 accelerate administrative processes and reduce waiting times at ports, thereby helping to reduce logistics costs. The transformation of INSW into Lembaga National Single Window (LNSW) strengthens the integration and coordination of the national logistics system. With multimodal and digitized processes, logistics cost efficiency is expected to improve, supporting Indonesia's economic growth and competitiveness.